Exploring the morphological and morphometric characteristics of the mandibular lingula in dry mandibles of South African population - Sethabile Nkabinde; Brenda Zola De Gama; Sundika Ishwarkumar-Govender; Pamela Pillay (Elsevier, 2024)
Background: The lingula of the mandible is a small tongue-shaped bony prominence that partially overlaps the mandibular foramen. It has variable shapes among different populations which impacts its significance as a bony landmark in maxillofacial and oral surgeries. This study aimed to explore the morphological and morphometric characteristics of the mandibular lingula in dry mandibles of a South African population, to provide more knowledge on its structural variations, and location for surgeons involved with maxillofacial and oral surgeries. Methodology: The study utilized 45 (n = 90 sides) dry human mandibles. The shapes were classified into five types, as per the classification scheme proposed by Tuli et al. (2000) and Varma and Sameer (2013). Three morphometric parameters were utilized to determine the location of the lingula. A p-value of <0.05 was considered statistically significant. Results: The most common type of the lingula was the truncated type 36/90 (40%), followed by the triangular type 23/90 (25.56%) and, nodular type 22/90 (24.44%). The mean height (mean ± SD) of the lingula was 7.57 ± 1.56 mm. The mean distance from the lingula to the anterior border of the mandibular ramus was 20.05 ± 3.25 mm while the mean distance from the lingula tip to the posterior border of the ramus of the mandible was 16.58 ± 2.26 mm. The mean distance was 15.81 ± 2.15 mm from the lingula to the mandibular notch. Conclusion: The present study contributes to the existing body of knowledge on the structural variation of the lingula which is important for precise location of the mandibular foramen and related structures, especially when performing any maxillofacial surgical procedures within a South African population group.